Uzupełnij puste miejsce tak, aby równianie było tożsamościowe :
a) 3x + ... = x - 2
b) 3 - x = 2 + ...
c) -(...) + x= 5 - x

Rozwiąż równanie :
a) (√2x - 1)(√2x + 1) = (√2x - √5x)² + 2(√10x - 3) - (4 - x)
w tym przykładzie ma wyjść 4.

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-24T15:50:02+01:00
A) 3x + 2 = x - 2
b) 3 - x = 2 + x
c) -(-5) + x= 5 - x


Rozwiąż równanie :
a) (√2x - 1)(√2x + 1) = (√2x - √5x)² + 2(√10x - 3) - (4 - x) |x √10
(20x-1)(20x+1)= (20x-2x)² + 2(x-3)- (4-x)
400x= 400x- 4x+ 2x-6-4+x
400x - 400x + 4x -2x -x= -6
x= -6